Development and validation of the newborn clubfoot screening checklist to improve the detection of postnatal congenital talipes equinovarus among newborns by non- orthopaedic-trained healthcare workers in Sarawak general Hospital a cross-sectional prospective study - Haniza Sahdi; Ravin Prabaharan; Whye Lian Cheah; Ahmad Hata Rasit; Mohamad Adam Bujang; Nur Alyana Benjamin Abdullah (Journal of the Academy of Family Physicians of Malaysia and Family Medicine Specialist Association of Malaysia, 2024)
Introduction: Non-orthopaedic-trained healthcare professionals face challenges in identifying postnatal clubfoot deformities due to the lack of suitable assessment tools, resulting in misdiagnosis. Therefore, this study aimed to develop and validate the Neonatal Clubfoot Screening Checklist (NCSC) to assist non-orthopaedic-trained healthcare professionals in postnatal clubfoot assessment. Methods: The NCSC development involved five phases: conceptual understanding of deformity components, creation of pictorial representations, tool structure design, content and face validation, pilot study and field study. A cross-sectional prospective study was conducted in Sarawak General Hospital from January to June 2021. Non-orthopaedic-trained healthcare professionals were randomly assigned to two groups: one utilising the NCSC for newborn screening and another without it. Results were compared with assessments by the paediatric orthopaedic team. Kappa agreement tests and sensitivity and specificity analyses were performed to evaluate the tool’s reliability and validity, respectively. Results: The content and face validity were satisfactory. Six hundred twelve feet were screened using the NCSC, and 596 feet were checked without the tool. The kappa agreement tests showed strong concordance (kappa coefficient=0.725–1.000, P<0.001) between the non-orthopaedic- trained personnel and paediatric orthopaedic team for all NCSC items. The NCSC exhibited 100% sensitivity, specificity and positive and negative predictive values. Conclusion: The NCSC is a reliable tool for postnatal clubfoot screening, offering high sensitivity and specificity. It facilitates accurate differentiation of true-positive congenital talipes equinovarus from other foot conditions, reducing misdiagnoses and unnecessary referrals. The NCSC is valuable in resource-constrained settings and for healthcare professionals lacking specialised orthopaedic training.